Model Pembinaan Karakter Religius Pada Anak Melalui Program Persada Di Tpa/Tpq Se-Kota Sorong - Andi Ahriani; Alga Amas Saputra; Zhaahir Awalun Ismail; Siti Faridah Datu (Kifah: Jurnal Pengabdian Masyarakat, 2026)
This article describes the objectives of the community service activity aimed at strengthening the religious character of children through the Saturday-Sunday Islamic Boarding School (Persada) program implemented at TPA/TPQ across Sorong City. This program emphasizes collaboration between TPA/TPQ leaders, parents, the community, BKM, and KKN students to create an environment that supports the formation of strong religious character in children. The method employed is a community-based approach involving educational activities such as tahfidz competitions, adzan competitions, and coloring contests, as well as evaluation through Focus Group Discussions (FGD). The results of the service show that the Persada program is effective in enhancing children's religious understanding and strengthening their religious character. The conclusion of this activity is that collaboration between various parties can accelerate the strengthening of children's religious character through structured and enjoyable learning.